Knowledge about Obstetric Danger Signs and Associated Factors among Antenatal Care Attendants - Mulugeta Shegaze (Intelektual Pustaka Media Utama, 2017)
Knowledge of mothers about obstetric danger sign is the basic influencing factor for utilization of skilled maternal and neonatal cares which reduce maternal and new born mortality and morbidity. Therefore this study intended to assess knowledge about obstetric danger sign and identify associated factors among antenatal care attendants. Institutional based cross- sectional study was conducted from April to June 2015 among 358 randomly selected antenatal care attendants. Epi Info version 7 and SPSS version 20 software were used for data entry and analysis respectively. Logistic regression was run to look for the association between dependent and explanatory variables; and using variables which have p-value ≤ 0.25 binary logistic regression was fitted. Association presented in Odds ratio with 95% confidence interval and significance determined at P-value less than 0.05. Most of the respondents able to name some of the accepted danger signs. Two hundred eight (58%), 182(51%) and, 161(45%) of mother were knowledgeable for obstetric danger sign which could occur during pregnancy, at child birth and post-partum period respectively. The most mentioned dander signs were bleeding, retained placenta and prolonged labor. The factors that associated with Knowledge of obstetric danger signs were urban residence (AOR=2.6; 95% CI: 1.8, 4.2), being literate (AOR=2.54; 95% CI: 1.14, 5.76), multiparity (AOR 1.5; 95% CI: 1.14, 2.3) and being informed (AOR=3; 95% CI: 1.6, 6.4). The study showed that attendant’s knowledge was low. This could be averted through strategies designed to address women’s through health extension workers and health professionals.